Cardiac Arrest in the Airport Revealing Cocaine Body Packing: A Case Report. (6th January 2019) - Resiere, Dabor; Mehdaoui, Hossein; Megarbane, Bruno
Abstract : Ingestion of large amounts of cocaine packages is a well-known method for cross-border transportation. Intestinal obstruction and life-threatening sympathomimetic toxidrome including seizures, ventricular dysrhythmia, and cardiac arrest resulting from the rupture of cocaine packages may occur. Here, we report a case of a 34-year-old pregnant woman who had a sudden cardiac arrest while waiting for her bags at Paris-Charles de Gaulle Airport, France. According to the flight attendants, the patient travelled from Brazil and complained of abdominal pain during the flight. After resuscitation, the patient presented sustained tachycardia and convulsions suggesting cocaine overdose caused by body packing. Once admitted to the hospital, laparotomy was performed allowing the extraction of 50 cocaine packages. Cardiac symptoms were attributed to the rupture of five of the packages. Prehospital and emergency physicians need to be aware of the possibility of cocaine overdose by body packing in patients presenting sudden cardiac arrest in airports.